Stability of Naked Nucleic Acids under Physical Treatment and Powder Formation: Suitability for Development as Dry Powder Formulations for Inhalation - Tomoyuki Okuda; Maki Okazaki; Akihiko Hayano; Hirokazu Okamoto (MDPI AG, 2023)
A number of functional nucleic acids, including plasmid DNA (pDNA) and small interfering RNA (siRNA), have been attracting increasing attention as new therapeutic modalities worldwide. Dry pDNA and siRNA powder formulations for inhalation are considered practical in clinical applications for respiratory diseases. However, physical stresses in the powder-forming process may destabilize nucleic acids, particularly when vectors with stabilizing effects are not used. We herein compare the stability of naked pDNA and siRNA through various physical treatments and two powder-forming processes. The structural and functional integrities of pDNA were markedly reduced via sonication, heating, and atomization, whereas those of siRNA were preserved throughout all of the physical treatments investigated. Spray-dried and spray-freeze-dried powders of siRNA maintained their structural and functional integrities, whereas those of pDNA did not. These results demonstrate that siRNA is more suitable for powder formation in the naked state than pDNA due to its higher stability under physical treatments. Furthermore, a spray-freeze-dried powder with a high content of naked siRNA (12% of the powder) was successfully produced that preserved its structural and functional integrities, achieving high aerosol performance with a fine particle fraction of approximately 40%.